MOTOR VEHICLE TAX COMPLIANCE: MEASURING DETERMINING FACTORS - Sulistyawati, Ardiani Ika; Sujarwati, Intan; Santoso, Aprih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study seeks to investigate the determinants of vehicle taxpayer compliance motorized in Semarang based on attribution theory and learning theory. The sample is 100 motor vehicle taxpayers in Semarang. Using multiple linear regression equation modeling, this study shows that the factors: knowledge and understanding of taxpayers, taxpayer awareness, services quality and tax sanctions effect motor vehicle taxpayer compliance in Semarang. Other findings indicate that the taxpayer awareness factor is the biggest factor in effect motor vehicle taxpayer compliance in Semarang. Keywords: knowledge, understanding, awareness, service